Pseudomonas eradication and clinical effectivness of Ivacaftor in four Hispanic patients with S549N. Issue 7 (3rd April 2017) - Strang, Abigail; Fischer, Anthony J.; Chidekel, Aaron
Summary: Ivacaftor was approved for rarer class‐III CFTR mutations including S549N in 2014. Since these mutations are uncommon, ongoing reports of patient experiences with Ivacaftor and these mutations are important. This case series describes the clinical effectiveness (including airway infection status, lung function, and growth) of Ivacaftor therapy in four pediatric Hispanic patients with S549N and F508del over 24 months. In these patients, Ivacaftor was highly efficacious with no further Pseudomonas ‐positive cultures despite prior chronic colonization in three patients as well as notable improvements in lung function and growth. The remarkable improvements in lung function and growth were similar to G551D patients with more striking changes in airway infection status.Pediatr Pulmonol 2017;52:E37–E39. © 2017 Wiley Periodicals, Inc.